Environmental control of phenological development in two Lesquerella species - Windauer, Liliana (2006)
Lesquerella fendleri and Lesquerella mendocina are two species with potential for domestication as crops for semiarid regions. Understanding the environmental influences on development is a critical step for the introduction of a wild species into cultivation. Under controlled conditions these species responded differently to temperature: L. fendleri phenological approach toward flowering responded linearly to temperature, whereas initiation of flowering in L. mendocina was relatively insensitive to temperature. L. fendleri exhibited a quantitative response to supra-optimal temperatures (with rate of development reduced with further increases in temperature) whereas L. mendocina showed a qualitative response, no flower development at supra-optimal temperatures. In this work undertaken in the field we studied phenological development in L. fendleri and L. mendocina as a function of planting date, quantified the time required to reach particular phenological stages under the various thermal environments, and compared these results with those previously obtained with controlled conditions. We also studied the influence of photoperiod on plant phenology in field situations and through experiments done under controlled conditions. Development rate for both species varied with sowing date with plant cycles shorter in spring sown plants, even if measured in thermal time. L. mendocina plants sown in late spring displayed a biennial cycle. These results are consistent with those obtained under controlled conditions. However, cycle shortening in thermal time with delays in sowing date suggested that factors other than temperature also influenced phenology of these two species. Further studies under controlled conditions showed that phenological development of L. fendleri plants was also altered by photoperiod, with plants displaying a typical long-day response. At the highest temperatures used in these studies L. mendocina plants did not respond to photoperiod. The possibility that incident radiation is involved in L. mendocina response to sowing date is discussed.